(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2024)
Shallot cultivation carried out by farmers in Oba District, Tidore Islands City or what is usually called the Trans-Koli area has become the main source of income for them and provides income to meet their daily needs. This research aims to analyze the shallot supply chain system and analyze the level of efficiency of the shallot supply chain in the Koli Transmigration Settlement Unit (UPT) area, Oba District, Tidore City, Islands, North Maluku Province. This research is survey research using a quantitative descriptive method approach. Qualitative analysis, namely analyzing the shallot supply chain used in this research, namely using supply chain efficiency analysis, then describing the shallot supply chain efficiency data. The research results explain that there are 3 (three) forms of shallot supply chain channels in Koli Transmigration, namely: channel I; farmers – traders, sub-district lura collectors – consumers, channel II; farmers, sub-district collectors – retailers – consumers and channel III, namely farmers – wholesalers – consumers. The marketing channels in the shallot supply chain flow in Koli Transmigration are efficient marketing channels because the efficiency value in each marketing channel is <5%. Where the efficiency value in channel I is 3.84%, channel II 4.69% and channel III 3.82%..